ANALISIS KONTRIBUSI PAJAK PARKIR DAN PAJAK RESTORAN DALAM RANGKA MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) JAKARTA TIMUR SERTA KONTRIBUSI TERHADAP PENDAPATAN ASLI DAERAH (PAD) DKI JAKARTA DALAM SEKTOR PAJAK PARKIR DAN PAJAK RESTORAN - Rina Hidayahti; Mulia Rahmah (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2018)
This research is to find out how big the tax contribution of parking and restaurant in order to increase tax Income Native (PAD) in East Jakarta, as well as how large the tax contribution of parking and restaurant Tax Revenue against the Original East Jakarta area (PAD) DKI Jakarta in the tax sector, parking and restaurant tax. This research was conducted at the Suku Badan Pajak dan Retribusi Daerah. This research is a qualitative descriptive study. Data taken from the Regional Original Revenue Report (PAD) in the form of targets and realization of East Jakarta's parking tax and restaurant tax 2015-2017. The analysis used is descriptive analysis using the ratio of parking tax contribution and restaurant tax. Data collection in the study was obtained from observation, interviews and documentation. The conclusion of this study, shows that the average contribution given Parking Tax and Restaurant Tax in order to increase the East Jakarta Regional Original Revenue (PAD) in 2015-2017 is 0.88% for Parking Tax with the criteria of "Very Less" and 4,88% for Restaurant Tax with "Very Less" contribution criteria. Whereas the average contribution given by the East Jakarta Parking Tax and Restaurant Tax to the DKI Jakarta Original Regional Income (PAD) in the Parking Tax and Restaurant Tax sectors in 2015-2017 is 6.48% for Parking Tax with the "Very Less" contribution criteria and 6.61% for Restaurant Tax with "Very Less" contribution criteria. Suggestions from this study, it is expected that East Jakarta Regional Tax and Retribution Agency must periodically re-record the parking taxpayer and restaurant, it is necessary to conduct socialization about the importance of compliance and awareness of taxpayers in making tax payments in accordance with the stipulated time and must be able to apply strict sanctions against taxpayers who are in arrears in order to achieve a deterrent effect on violators.